Opioid-Induced Respiratory Depression in Pediatric Palliative Care Patients with Severe Neurological Impairment-A Scoping Literature Review and Case Reports - Maximilian David Mauritz; Carola Hasan; Larissa Alice Dreier; Pia Schmidt; Boris Zernikow (MDPI AG, 2020)
Pediatric Palliative Care (PPC) addresses children, adolescents, and young adults with a broad spectrum of underlying diseases. A substantial proportion of these patients have irreversible conditions accompanied by Severe Neurological Impairment (SNI). For the treatment of pain and dyspnea, strong opioids are widely used in PPC. Nonetheless, there is considerable uncertainty regarding the opioid-related side effects in pediatric patients with SNI, particularly concerning Opioid-Induced Respiratory Depression (OIRD). Research on pain and OIRD in pediatric patients with SNI is limited. Using scoping review methodology, we performed a systematic literature search for OIRD in pediatric patients with SNI. Out of n = 521 identified articles, n = 6 studies were included in the review. Most studies examined the effects of short-term intravenous opioid therapy. The incidence of OIRD varied between 0.13% and 4.6%; besides SNI, comorbidities, and polypharmacy were the most relevant risk factors. Additionally, three clinical cases of OIRD in PPC patients receiving oral or transdermal opioids are presented and discussed. The case reports indicate that the risk factors identified in the scoping review also apply to adolescents and young adults with SNI receiving low-dose oral or transdermal opioid therapy. However, the risk of OIRD should never be a barrier to adequate symptom relief. We recommend careful consideration and systematic observation of opioid therapy in this population of patients.